DATA PRIVACY AND CONSTITUTIONAL RIGHTS IN INDONESIA: DATA PRIVACY AND CONSTITUTIONAL RIGHTS IN INDONESIA - Widodo, Junaidi Eko; Suganda, Atma; Tubagus Achmad Darodjat (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This article explores the connection between data privacy and constitutional rights in Indonesia, particularly within the framework of a democratic rule of law. The 1945 Constitution of Indonesia guarantees citizens' fundamental rights, including security and privacy. However, the rapid advancement of information technology has introduced new challenges for personal data protection. Currently, Indonesia's regulations, such as the Electronic Information and Transaction Law (ITE Law), lack comprehensive measures to safeguard data privacy rights, as they are sectoral and fragmented. This article highlights the necessity of enacting the Personal Data Protection Bill (RUU PDP) as a crucial step in strengthening the legal framework for data privacy protection in Indonesia. Additionally, it compares international regulations like the General Data Protection Regulation (GDPR) in the European Union, as well as data protection laws in neighboring countries like Singapore and Malaysia. The article underscores that prioritizing the protection of personal data privacy rights is essential for safeguarding constitutional rights and individual dignity, as well as for fostering a secure and trustworthy digital ecosystem in Indonesia.